Komunikasi Getok Tular dan Metode Dakwah Hizbut Tahrir Indonesia - Udin, Muhammad Diak; Muhid, Abdul (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2018)
This study aims to explain how the use of word of mouth communication (getok tular) and the rationale behind the usage as a method of da’wah within Hizbut Tahrir Indonesia (HTI). This study used a qualitative approach with a case study design. The results of the study revealed that the word of mouth communication was applied for two activities, namely as a method of delivering da’wah messages and as a method of cadre with a chain system to official members who were stratified based on the study book or HTI curriculum. The reason why HTI used word of mouth communication as a method of da’wah was because of the effectiveness and efficiency factors as well as socio-cultural factors.